Biomechanics and hydrodynamics study od aquatic locomotion - Yaakob, Omar; Ibrahim, Zaharah; Priyanto, Agoes; Omar, Mohd. Shahir Shamir; Adnan, Faizul Amri; Hamdan, Salehuddin; Md. Salleh, Madihah; Abdul Wahap, Mohd. Arizam (Faculty of Mechanical Engineering, 2008)
This study was conducted in order to characterize propulsion and control surface (caudal fin) of Anabas testudineus (puyu) based on distance travelled, resultant speed and acceleration. Fish was trained to swim along a 2 x 1 feet long aquarium. Two fish (adult and juvenile) were kept in the aquarium at a time to stimulate a competitive situation and induce burst swimming sequences. Spontaneous swimming along the aquarium was filmed and analysed. A CCV-A11b (Progressive Scan Monochrome Camera) was positioned 180 cm above the base of the aquarium to provide dorsal views of swimming sequences. Images from video recordings (20 frames sÂ¯Â¹) were analysed frame by frame using global coordinates system, with time interval 0.05s. When sub-carangiform alone was used it was found that in both juvenile and adult, the distance travelled by the tail tip was always greater than the distance travelled by the body. In contrast, when sub-carangiform was used in combination with labriform locomotion, the distance travelled by tail tip was less than the distance travelled by the body, which is comparable to the double propulsion system found in marine vehicles. Apart from that, other findings revealed that juvenile fish had higher acceleration rate compared to an adult for a given time. Overall, A. testudineus were more efficient swimmers in their juvenile forms than in adulthood based on their distance travelled, speed, acceleration and distance travelled ratio.